Heteroatom‐Doped Carbon Nanotube and Graphene‐Based Electrocatalysts for Oxygen Reduction Reaction. Issue 45 (29th September 2017) - Li, Jin‐Cheng; Hou, Peng‐Xiang; Liu, Chang
Abstract: Oxygen reduction reaction (ORR) is a key step that determines the performance of a variety of energy storage and conversion devices, such as fuel cells and metal–air batteries. Heteroatom‐doped carbon nanotubes (CNTs) and graphenes have attracted increasing interest and hold great promise as efficient ORR catalysts to replace noble‐metal‐based catalysts, owing to their unique structure characteristics, excellent physicochemical properties, low cost, and rich resources. In this review, recent progress on the design, fabrication, and performance of heteroatom‐doped CNT‐ and graphene‐based catalysts is summarized, aiming to provide insights into the working mechanism of these heteroatom‐doped nanocarbons in ORR. The advantages, challenges that remain, and possible solutions of these nanocarbon‐based electrocatalysts are discussed. Finally, future developing trends of the CNT‐ and graphene‐based ORR catalysts are proposed. Abstract : Carbon nanotubes (CNTs)/graphenes are unique one‐dimensional/two‐dimensional structures composed of sp 2 hybridized carbon atoms and excellent physicochemical properties. Heteroatom‐doped CNT/graphene‐based catalysts show advantages of high‐content active sites, good electron/ion transport capability, excellent durability, and low cost. These catalysts demonstrate attractive oxygen reduction reaction performance and therefore may find applications in metal–air batteries and fuel cells.